Embedding violence prevention in existing religious and education systems: initial learning from formative research in the Safe Schools Study in Zimbabwe - Emily Eldred; Ellen Turner; Camilla Fabbri; Amiya Bhatia; Michelle Lokot; Tendai Nhenga; Charles Nherera; Progress Nangati; Ratidzai Moyo; Dorcas Mgugu; Robert Nyakuwa; Sarah Rank; et al. (BMC Public Health)
Abstract Background Few interventions to reduce violence against children in Catholic Church affiliated schools have been tested for effectiveness. We describe learning from formative research on the development of a school-based behavioural intervention aiming to reduce teacher violence and bullying, which originated from and is embedded within Catholic-run primary schools in Zimbabwe. Specifically, we aim to (1) describe and document the process of intervention development and refinement, including efforts to design the Safe Schools Programme to be embedded into existing religious, child protection, and education structures; (2) reflect on the opportunities and challenges of developing a violence prevention intervention for integration within existing education and religious systems; and (3) discuss the implications for scale-up and sustainability of violence prevention interventions. Methods We conducted multi-method research to understand the context of intervention implementation, the acceptability of the intervention, feasibility of the delivery model and to refine both the intervention content and underlying intervention theory of change. This included Theory of Change workshops with all study partners at three time-points, and focus groups, in-depth interviews, participatory workshops at two time-points. Participants in qualitative research included school headteachers, teachers, school staff, priests, students, parents, local government education actors, and child protection NGO staff. Qualitative data were analysed thematically. Results Findings reveal several challenges facing schools including low motivation of teachers due to high workload and inadequate school-based referral systems for child protection. Views on the acceptability of corporal punishment are polarised with some parents and teachers supporting its use despite the recent ban, presenting an opportunity for the intervention to support teachers move towards alternative discipline. Findings suggest that aligning intervention activities within existing structures within schools and using familiar teaching methods is an effective way to support intervention uptake while addressing concerns about teachers’ workload and intervention acceptability. The intervention was refined in light of the qualitative findings and Theory of Change workshop reflections, which included: additional behaviour change engagement with teachers, an amendment of the school-based referral system, amendment of manual content for children, and streamlining of materials with existing workload. Conclusions Interventions designed by ‘insiders’ at institutions such as the Catholic Church, have huge potential for implementation at a large scale due to systems and context expertise, pre-established relationships, and alignment with stakeholder priorities. However, such interventions should be mindful of power hierarchies and provide adequate support to equip actors with violence prevention expertise. Future research on violence prevention interventions designed by religious institutions and their implications for future scale-up and sustainability is recommended.